Fibrin formation by staphylothrombin facilitates Staphylococcus aureus-induced platelet aggregation - Vanassche, Thomas; Kauskot, Alexandre; Verhaegen, Jan; Peetermans, Willy E.; van Ryn, Joanne; Schneewind, Olaf; Hoylaerts, Marc F.; Verhamme, Peter (Thrombosis and Haemostasis, 2012)
Interactions of Staphylococcus aureus (S. aureus) and platelets play an important role in the pathogenesis of intravascular infections such as infective endocarditis (IE). A typical feature of S. aureus is the ability to generate thrombin activity through the secretion of two prothrombin activating molecules, staphylocoagulase and von Willebrand factor-binding protein (vWbp), which bind to human prothrombin to form the enzymatically active staphylothrombin complex. The role of staphylothrombin in the interaction between S. aureus and platelets has not yet been studied. We found that in contrast with thrombin, staphylothrombin did not directly activate human platelets. However, the staphylothrombin-mediated conversion of fibrinogen to fibrin initiated platelet aggregation and secondary activation and facilitated S. aureus-platelet interactions. Both the genetic absence of staphylocoagulase and vWbp and pharmacological inhibition of staphylothrombin increased the lag time to aggregation, and reduced platelet trapping by S. aureus in high shear stress conditions. The combined inhibition of staphylothrombin and immunoglobulin binding to platelets completely abolished the ability of S. aureus to aggregate platelets in vitro. In conclusion, although staphylothrombin did not directly activate platelets, the formation of a fibrin scaffold facilitated bacteria-platelet interaction, and the inhibition of staphylothrombin resulted in a reduced activation of platelets by S. aureus.
Keywords: Staphylococcus aureus; staphylothrombin; thrombin; infective endocarditis; platelet activation